Flipped Learning in Foreign Language Learning in Higher Education: Analysis of Effectiveness and Moderator Variables - Ulum, Fatkhul; Hukom, Julham (Jurnal Pendidikan Progresif, 2025)
Flipped Learning in Foreign Language Learning in Higher Education: Analysis of Effectiveness and Moderator Variables. Many studies have reported that the flipped learning strategies has a significant effect on students' foreign language skills in college compared to traditional learning strategies. However, reports regarding the effectiveness of flipped learning strategies in foreign language learning are very heterogeneous. Objectives: Based on this empirical gap, this study aims to synthesize the application of flipped learning strategies in students' foreign language learning in higher education compared to traditional learning strategies. Method: This study uses the meta-analysis method to answer the objectives of this study. Findings: The results of the analysis of twelve research samples with a random-effect estimation model show that the use of the flipped learning strategies has a more significant effect on students' foreign language skills in college when compared to traditional strategies, with the combined effect size value being in the large effect category (g = 0.89; p < 0.05). In addition, the results of the moderator factor analysis show that the variables of flipped learning class capacity, ability type, and foreign language type significantly affect the effectiveness of the use of the flipped learning strategies to students' diverse foreign language skills. Conclusion: These reports provide strong evidence as recommendations for educators, researchers and educational policy makers regarding the application of flipped learning strategies in foreign language learning in higher education. Regardless of the validity of the results, this study only involved a few research samples. Further research is recommended to combine more samples, or focus on the type of abilities measured, so that it can provide more specific conclusions. Keywords: effect size, foreign language, flipped learning, meta-analysis, moderator variable.